2007
DOI: 10.1007/s10995-007-0285-1
|View full text |Cite
|
Sign up to set email alerts
|

Homeless Women: Who is Really at Risk for Unintended Pregnancy?

Abstract: Objective To identify correlates of failure to use contraception among homeless women at risk for unintended pregnancy. Study Design A representative sample of 974 homeless women surveyed in Los Angeles County in 1997 included 457 who were at risk for unintended pregnancy. Logistic regression modeling was used to identify important predictors of contraceptive nonuse or rare use in the past year. Results One third of the sample used contraception rarely or never in the past year. Having a partner, being monogam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 25 publications
0
43
0
Order By: Relevance
“…9 Among the homeless women using contraception, 92% relied primarily on condoms and only 32% of those reported using condoms with every sexual encounter. 10 In contrast, approximately 50% of all pregnancies in the United States are unintended and only 10% of women in the general population practicing contraception used condoms as their most effective method of birth control. 11,12 …”
mentioning
confidence: 99%
“…9 Among the homeless women using contraception, 92% relied primarily on condoms and only 32% of those reported using condoms with every sexual encounter. 10 In contrast, approximately 50% of all pregnancies in the United States are unintended and only 10% of women in the general population practicing contraception used condoms as their most effective method of birth control. 11,12 …”
mentioning
confidence: 99%
“…To date, most extant research efforts have cross-sectionally examined pregnancy prevalence and associated risk factors among homeless women, most frequently investigating topics such as contraception use and risky sexual activity (Gelberg et al, 2008;Halcón & Lifson, 2004;Solorio et al, 2008;Thompson et al, 2008;Unger et al, 1998).…”
Section: Homeless Youth Pregnancymentioning
confidence: 99%
“…Highlighting some examples, in a representative sample of 974 homeless women (of all ages), one-third reported rare or no use of contraception in the prior year despite sexual activity, citing barriers that were positively correlated to contraception non-use, such as not knowing how to use contraceptives and contraception cost (Cauce et al, 2005;Gelberg et al, 2008;Hathazi et al, 2009). In another study, 42% of sexually active homeless women said they did not use any form of birth control in the prior 12 months (Arangua, Andersen, & Gelberg, 2005), while researchers have found that 95% of homeless females are sexually active (Nyamathi, 1993).…”
Section: Homeless Youth Pregnancymentioning
confidence: 99%
“…Researchers have advised service providers to make available physical health (Gelberg et al, 2008), mental health (Christensen et a l., 2005), substance abuse (Kertesz et al, 2007), case management (Desai & Rosenheck, 2005), nutrition planning (Richards & Smith, 2006), contraception and family planning (Gelberg et al, 2008), syringe exchange (Heller et al, 2009), and oral health (Conte et al, 2006) services to members of this population. Some have made specific policy recommendations as well (Richards & Smith, 2006).…”
Section: Introductionmentioning
confidence: 99%